Stories by English Authors: London (Selected by Scribners) - Anstey, F., 1856-1934; Barrie, J. M. (James Matthew), 1860-1937; Corelli, Marie, 1855-1924; Harraden, Beatrice, 1864-1936; Morrison, Arthur, 1863-1945; Quiller-Couch, Arthur, 1863-1944; Zangwill, Israel, 1864-1926 (Salt Lake City, UT : Project Gutenberg, 2006)
"Stories by English Authors: London" by F. Anstey et al. is a collection of short stories compiled in the early 20th century. The book presents various narratives exploring themes of social class, human behavior, and everyday dilemmas through comedic and poignant lenses, all set against the backdrop of London life. Among the featured tales is "The Inconsiderate Waiter" by J.M. Barrie, which humorously portrays the peculiar relationship between a member of a private club and his long-suffering waiter, William. The opening of "The Inconsiderate Waiter" introduces us to the protagonist, a club member who reflects on his seemingly trivial yet revealing interactions with his waiter, William. The narrative begins with the member's disdain for oysters, which William, who once understood his preferences, inexplicably serves him, leading to the protagonist's growing irritation. As the scene unfolds, we learn that William is deeply concerned for his sick wife, a fact that disrupts the member's well-ordered life and dining experience. This initial setup sets the stage for a deeper exploration of class distinctions, personal connections, and the often unnoticed lives of those in service roles, blending humor with social commentary. (This is an automatically generated summary.)
The Inconsiderate Waiter, By J. M. Barrie -- The Black Poodle, By F. Anstey -- That Brute Simmons, By Arthur Morrison -- A Rose Of The Ghetto, By I. Zangwill -- An Idyl Of London, By Beatrice Harraden -- The Omnibus, "Q" [Quiller-Couch] -- The Hired Baby, By Marie Correlli
Release date is 2006-03-26
Produced by Dagny; John Bickers and David Widger
Keywords: London (England) -- Fiction; Short stories, English